Bringing Forth Treasures New and Old: Xu Caibai, a Forgotten Chinese Jesuit Bible Translator - Moss, Michael E. (Journal of Jesuit studies, 2026)
Although the recent rediscovery of a manuscript containing a translation of the Four Gospels into literary Chinese by Fr. Xu Caibai, a nineteenth-century Chinese priest who joined the Society of Jesus in 1862 and left it to become a diocesan priest in 1884, has given rise to renewed interest toward this remarkable but neglected figure in the history of the Chinese church, precious little work has been done to this day. To remedy this gap, in this paper we will attempt as thorough a reconstruction of his biography as allowed by the sources available to us and provide an analysis of the historical context in which it was produced, both with regards to historical Catholic policies on vernacular Bible translation and the specific context of the mission in Jiangnan, while pointing out several remarkable aspects of his unpublished translation. By comparing Xu’s work to Manuel Dias’s early exegetical work on Sunday Gospel readings, the classic commentaries of Giovanni Stefano Menochio, those of French Oratorian priest Louis de Carrières, and his contemporary Li Wenyu’s translation of the Four Gospels, we will show how Xu strove to weave a rich tapestry in which the legacy of seventeenth-century Jesuit translation is combined with the contributions of French missionaries of the restored Society.